CB2 receptor antibody signal specificity: correlations with the use of partial CB2-knockout mice and anti-rat CB2 receptor antibodies - Zhang Hai-ying; Shen Hui; Jordan Chloe J.; Liu Qing-rong; Gardner Eliot L.; Bonci Antonello; Xi Zheng-xiong (Acta Pharmacologica Sinica, 2019)
Cannabinoid CB1 receptors are highly expressed in the brain and functionally modulate presynaptic neurotransmitter release, while cannabinoid CB2 receptors (CB2Rs) were initially identified in the spleen and regarded as peripheral cannabinoid receptors. Recently, growing evidence indicates the presence of functional CB2Rs in the brain. However, this finding is disputed because of the specificity of CB2R antibody signals. We used two strains of currently available partial CB2-knockout (CB2-KO) mice as controls, four anti-rat or anti-mouse CB2R antibodies, and mRNA quantification to further address this issue. Western blot assays using the four antibodies detected a CB2R-like band at ~40 kD in both the brain and spleen. Notably, more bands were detected in the brain than in the spleen, and specific immune peptides blocked band detection. Immunohistochemical assays also detected CB2-like immunostaining in mouse midbrain dopamine neurons. CB2R deletion in CB2-KO mice may reduce or leave CB2R-like immunoreactivity unaltered depending on antibody epitope. Antibodies with epitopes at the receptor-deleted region detected a significant reduction in CB2R band density and immunostaining in N-terminal-deleted Deltagen and C-terminal-deleted Zimmer strain CB2-KO mice. Other antibodies with epitopes at the predicted receptor-undeleted regions detected similar band densities and immunostaining in wild-type and CB2-KO mice. Quantitative RT-PCR assays detected CB2 mRNA expression using probes that targeted upstream or downstream gene sequences but not the probe that targeted the gene-deleted sequence in Deltagen or Zimmer CB2-KO mice. These findings suggest that none of the tested four polyclonal antibodies are highly mouse CB2R-specific. Non-specific binding may be related to the expression of mutant or truncated CB2R-like proteins in partial CB2-KO mice and the use of anti-rat CB2 antibodies because the epitopes are different between rat and mouse CB2Rs.